2016
DOI: 10.1038/nnano.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of oligonucleotides of different lengths with a wild-type aerolysin nanopore

Abstract: Protein nanopores offer an inexpensive, label-free method of analysing single oligonucleotides. The sensitivity of the approach is largely determined by the characteristics of the pore-forming protein employed, and typically relies on nanopores that have been chemically modified or incorporate molecular motors. Effective, high-resolution discrimination of oligonucleotides using wild-type biological nanopores remains difficult to achieve. Here, we show that a wild-type aerolysin nanopore can resolve individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
332
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(345 citation statements)
references
References 31 publications
9
332
0
4
Order By: Relevance
“…Similar to previous reports, Long’s group in 2016 21 (see the detailed protocol of 2017 23 ) determined that ARP could not capture long, single-stranded DNA molecules, but this conductance variation could discriminate the length of high-concentrations (1 μM) of short (2–10 nt) poly(dA) oligonucleotides at a single nucleotide resolution (Fig. 2a) under a wide range of pH conditions where the ARP remained stable.…”
Section: Direct Discrimination Of a T C And G Nucleobases As Well supporting
confidence: 83%
See 2 more Smart Citations
“…Similar to previous reports, Long’s group in 2016 21 (see the detailed protocol of 2017 23 ) determined that ARP could not capture long, single-stranded DNA molecules, but this conductance variation could discriminate the length of high-concentrations (1 μM) of short (2–10 nt) poly(dA) oligonucleotides at a single nucleotide resolution (Fig. 2a) under a wide range of pH conditions where the ARP remained stable.…”
Section: Direct Discrimination Of a T C And G Nucleobases As Well supporting
confidence: 83%
“…19,20 Compared to other reported biological nano-pores, ARP exhibits the advantage of stability over a broad pH range. 21,22 …”
Section: Arp Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The technologies presented above show the future potential for the identification of epigenetic modification or single nucleotide polymorphism on DNA using the nanopore-nucleic acid interaction [52,53,61,62]. In addition, the nanopore coupled with a complementary DNA would facilitate the early detection of pathogenic DNA, shown in the detection of the anthrax-related DNA of Bacillus anthracis [63].…”
Section: Chemical and Biomolecular Sensingmentioning
confidence: 99%
“…It has been broadly investigated for various genetic, 1923 epigenetic, 2427 and proteomic 2830 detection strategies. 31 Many excellent studies have demonstrated nanopore’s single-nucleotide sensitivity 3234 and ability to detect single-nucleotide polymorphism.…”
mentioning
confidence: 99%